The Development of Chinese and Cuban Science Fiction in Comparative Perspective: From Colonialism to Revolution and Beyond - Laura Pimentel Barbosa (Contexto Internacional)
Abstract This essay explores the literary genre of science fiction as a tool for historical and political analysis, focusing specifically on the development and transformation of the genre in China and Cuba. Through an examination of the uses and themes of science fiction literature in these countries, we can gain a deeper understanding of how Enlightenment ideas and socialist ideals merged with nationalist aspirations for independence and development. Given the major socialist revolutions that took place in both China and Cuba, our essay compares the development of science fiction in these nations, exploring how the genre was employed to promote societal projects and the challenges faced in implementing them. In the latter part of the essay, we analyse two contemporary novels that reflect on these revolutions – Chan Koonchung’s The Fat Years and Eric Mota’s Habana Underguater – examining the values of independence, revolution and progress that inspired them. Our focus will be on how these stories articulate the promises and disappointments of their respective revolutions, the impact of the ‘new man’ concept on the quest for individuality, and the collective memory of revolutionary experiences.